Childhood adversity is linked to adult health among African Americans via adolescent weight gain and effects are genetically moderated. (August 2021) - Beach, Steven R. H.; Ong, Mei Ling; Lei, Man-Kit; Klopack, Eric; Carter, Sierra E.; Simons, Ronald L.; Gibbons, Frederick X.; Lavner, Justin A.; Philibert, Robert A.; Ye, Kaixiong
Abstract: Identifying the mechanisms linking early experiences, genetic risk factors, and their interaction with later health consequences is central to the development of preventive interventions and identifying potential boundary conditions for their efficacy. In the current investigation of 412 African American adolescents followed across a 20-year period, we examined change in body mass index (BMI) across adolescence as one possible mechanism linking childhood adversity and adult health. We found associations of childhood adversity with objective indicators of young adult health, including a cardiometabolic risk index, a methylomic aging index, and a count of chronic health conditions. Childhood adversities were associated with objective indicators indirectly through their association with gains in BMI across adolescence and early adulthood. We also found evidence of an association of genetic risk with weight gain across adolescence and young adult health, as well as genetic moderation of childhood adversity's effect on gains in BMI, resulting in moderated mediation. These patterns indicated that genetic risk moderated the indirect pathways from childhood adversity to young adult health outcomes and childhood adversity moderated the indirect pathways from genetic risk to young adult health outcomes through effects on weight gain during adolescence and early adulthood.